2006
DOI: 10.1097/01.mlr.0000215901.37144.94
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Care Among American Indians in Public Health Care Programs

Abstract: Although individuals have enrolled in health care programs and have access to care, barriers to using these services remain. Significant differences between AIs and Whites involve issues of trust, respect, and discrimination. Providers must address barriers experienced by AIs to improve accessibility, acceptability, and quality of care for AI health care consumers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 10 publications
3
103
0
Order By: Relevance
“…Patient-related factors may include mistrust of physicians or hospitals and lower satisfaction with healthcare [24][25][26][27]. Patients' risk perception of surgery may be central to their willingness to undergo resection and higher risk aversion has been suggested as a potential reason for under treatment among minorities.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-related factors may include mistrust of physicians or hospitals and lower satisfaction with healthcare [24][25][26][27]. Patients' risk perception of surgery may be central to their willingness to undergo resection and higher risk aversion has been suggested as a potential reason for under treatment among minorities.…”
Section: Discussionmentioning
confidence: 99%
“…24 In its report on disparities in health care, the Institute of Medicine found that Ïœ1% of the studies it reviewed had sample sizes large enough for meaningful analysis of AI/AN data. 25,26 Within the NIS, the sample of AI/AN children in any single year is relatively small, making it difficult to identify significant differences. Given this, our analysis illustrates the utility of looking for patterns over time, rather than focusing on a difference in any particular year.…”
Section: Methodologic Challengesmentioning
confidence: 99%
“…Plausible effects of poverty on maternal health that may translate to infant health have been well documented. For instance, residence in a high poverty neighborhood may diminish access to adequate nutrition, to culturally-appropriate and quality health care, or to reliable modes of communication and transportation (34)(35)(36). It is also possible that some or all of these things are available, but that circumstances in a high poverty neighborhood constrain one's options to choose only one in lieu of the others (37).…”
Section: Discussionmentioning
confidence: 99%